Cancer-Induced Alterations of NK-Mediated Target Recognition: Current and Investigational Pharmacological Strategies Aiming at Restoring NK-Mediated Anti-Tumor Activity - Chretien, Anne-Sophie; Le Roy, Aude; Vey, Norbert; Prebet, Thomas; Blaise, Didier; Fauriat, Cyril; Olive, Daniel (Frontiers in Immunology, 2014)
Despite evidence of cancer immune-surveillance, which plays a key role in tumor rejection, cancer cells can escape immune recognition through different mechanisms. Thus, evasion to NK cell mediated anti-tumor activity is commonly described and is mediated by various mechanisms, mainly cancer cell-induced down regulation of NK activating receptors (NCRs, NKG2D, DNAM-1 and CD16) as well as up regulation of inhibitory receptors (KIRs, NKG2A). Alterations of NK cells lead to an impaired recognition of tumor cells as well as a decreased ability to interact with immune cells. Alternatively, cancer cells down-regulate expression of ligands for NK cell activating receptors and up-regulate expression of the ligands for inhibitory receptors. A better knowledge of the extent and the mechanisms of these defects will allow developing pharmacological strategies to restore NK cell ability to recognize and lyse tumor cells. Combining conventional chemotherapy and immune modulation is a promising approach likely to improve clinical outcome in diverse neoplastic malignancies. Here, we overview experimental approaches as well as strategies already available in the clinics that restore NK cell functionality. Yet successful cancer therapies based on the manipulation of NK cell already have shown efficacy in the context of hematologic malignancies. Additionally, the ability of cytotoxic agents to increase susceptibility of tumors to NK cell lysis has been studied and may require improvement to maximize this effect. More recently, new strategies were developed to specifically restore NK cell phenotype or to stimulate NK cell functions. Overall, pharmacological immune modulation trends to be integrated in therapeutic strategies and should improve antitumor effects of conventional cancer therapy.